Pengaruh Kompetensi Dan Independensi Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderating (Studi Empiris Pada Kantor Badan Pengawasan Keuangan Dan Pembangunan Perwakilan D.I Yogyakarta) - SURYANTI, ARIFATUN; , Drs. Wahyono, Ak, MA (2015)
This study aims to determine the effect the competence and independence of the quality of the audit with the auditor ethics as moderating variable. Based on the results of the study are expected to provide input for the client and stakeholders to consider the factors that affect the auditor to be able to produce quality audit. This study used a survey method using primary data obtained from the questionnaire. The population in this study is the auditor who works in the Office of Financial and Development Supervisory Agency Representative Yogyakarta with convenience sampling method and obtained 38 auditors as research samples. Methods of data analysis using Moderated Regression Analysis. The results showed that: (1) Competence effect on audit quality and H1 statistically supported with 0.000 p-value<0.05. (2) The independence of impact on audit quality and H2 statistically supported with 0.003 p-value <0.05. (3) The interaction of the competence and ethics of auditors has no effect on audit quality and H3 supported statistically with p-value 0.099> 0.05. (4) Interaction auditor independence and ethical impact on audit quality and statistically supported H4 p-value 0.022 <0.05.